Relationship Between Global Stock Exchanges and Indian Stock Market - Mayur, Manas (Asian Journal of Empirical Research, 2017)
The Indian capital market has been always a subject of curiosity and research. Extensive research has been conducted over the years to predict the index, arguably till date no model could closely predict the index. It is also observed that the Indian stock market follows global cues which partially decide its direction for the day’s trading. Considering this fact, an attempt is made to study the global markets, to establish a mathematical model for forecasting the value of S&P BSE Sensex. The study employs a multiple regression model on daily stock prices of S&P BSE Sensex and few major global stock indices that would help an average investor to make an informed investment decision in Indian stock markets. It would act as a base for investors to take long term positions on the stocks traded on the exchange. The model would also help the policy makers to review key policy decisions based on global cues.